Fishery of goatfish at Visakhapatnam with some information on the biology of Upeneus vittatus (Forsskal) - Hamsa, K M S Ameer; Rao, K Narayana (Indian Journal of Fisheries, 2011)
The goatfish fishery at Visakhapatnam by small mechanised trawlers during 1994-'96 is presented. During the period the goat fishes formed 4.5 % of the total fish catch landed by the small mechanised trawlers. The fishery was sustained by Upeneus vittatus (65.1 %), U. sulphureus (26.5 %) and U. moluccensis (8.3 %). Upeneus vittatus feeds mainly on prawn, crab and Squilla spp. The females were observed in the maturity stages I - IV and the matured females were recorded in February, March, May and August. The length-weight relationship of U. vittatus is also described.